2014
DOI: 10.2147/dnnd.s37341
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic mechanisms in Alzheimer's disease

Abstract: Abstract:The worldwide increase in life expectancy is leading to an increase in age-dependent diseases, including nonfamilial, sporadic Alzheimer's disease (AD), which is the subject of this review. The etiology and pathophysiology of the disease is not fully understood, but present observations suggest that, in addition to genetic risk factors, environmental influences may be involved via epigenetic mechanisms. Currently, there is no effective treatment, but there are indications that lifestyle has an impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 174 publications
0
10
0
Order By: Relevance
“…Recently, it has been observed that environmental factors even transient ones in early life can induce AD-like pathogenesis in association with aging (Wu et al, 2008a ). Furthermore, a difference in DNA methylation patterns typical of brain region and aging has been identified in this context (Balazs, 2014 ). In this regard, a recent study by Hernandez et al examined the DNA methylation patterns in >27,000 CpG sites from donors ranging in age 4 months to 102 years and a strong relationship was found between DNA methylation and aging.…”
Section: Alzheimer’s Disease and Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been observed that environmental factors even transient ones in early life can induce AD-like pathogenesis in association with aging (Wu et al, 2008a ). Furthermore, a difference in DNA methylation patterns typical of brain region and aging has been identified in this context (Balazs, 2014 ). In this regard, a recent study by Hernandez et al examined the DNA methylation patterns in >27,000 CpG sites from donors ranging in age 4 months to 102 years and a strong relationship was found between DNA methylation and aging.…”
Section: Alzheimer’s Disease and Epigeneticsmentioning
confidence: 99%
“…The acetylation of histones is a modification associated generally to transcriptional activity that indicates access of the transcription machinery to the genes and thus active mechanisms (Strahl and Allis, 2000 ; Balazs, 2014 ). This effect could be explained by the chemistry of this modification in which an acetyl group (−COCH3) is incorporated to an amino terminal residue and thus, the positive charge of histones is reduced, inducing a minor interaction with DNA resulting in a decrease of the chromatin compaction (Figures 2A,B ; Shahbazian and Grunstein, 2007 ).…”
Section: Histone Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a fair chance that factors in addition to aging, eg, hypertension, diabetes, obesity, and inflammatory disorders, may have an effect on AD and be inducing epigenetic changes as well or might induce AD-like pathogenesis at a young age. Associations between DNA-methylation patterns in the brain and aging are possible44 and have been reported in various regions of the brain 45. Since DNA epigenetic mechanisms have a role in memory formation and its maintenance, just as decrease in DNA methylation deteriorates neuronal plasticity, leading to memory loss, it is speculated that understanding of epigenetic mechanisms is important to understand aging and associated complexities in AD patients 46.…”
Section: Epigenetics and Admentioning
confidence: 99%
“…Histone methylation and demethylation, mediated by histone methylases (HMTs) and demethylases (HDMTs), respectively, also contribute to neurodegenerative progression. Those enzymes have a high specificity as they usually modify one single lysine per histone which may be translated into activation or repression of transcription [ 19 , 55 , 101 , 102 , 124 , 125 ]. Histone methylations H3K4, H3K36, and H3K79 are associated with the activation of gene expression, whereas methylations at H3K9, H3K27, and H4K20, correspond to gene silencing.…”
Section: Main Epigenetic Hallmarks Of Neurodegenerationmentioning
confidence: 99%